Social media and physicians: Exploring the benefits and challenges. (June 2016) - Panahi, Sirous; Watson, Jason; Partridge, Helen
Healthcare professionals' use of social media platforms, such as blogs, wikis, and social networking web sites has grown considerably in recent years. However, few studies have explored the perspectives and experiences of physicians in adopting social media in healthcare. This article aims to identify the potential benefits and challenges of adopting social media by physicians and demonstrates this by presenting findings from a survey conducted with physicians. A qualitative survey design was employed to achieve the research goal. Semi-structured interviews were conducted with 24 physicians from around the world who were active users of social media. The data were analyzed using the thematic analysis approach. The study revealed six main reasons and six major challenges for physicians adopting social media. The main reasons to join social media were as follows: staying connected with colleagues, reaching out and networking with the wider community, sharing knowledge, engaging in continued medical education, benchmarking, and branding. The main challenges of adopting social media by physicians were also as follows: maintaining confidentiality, lack of active participation, finding time, lack of trust, workplace acceptance and support, and information anarchy. By revealing the main benefits as well as the challenges of adopting social media by physicians, the study provides an opportunity for healthcare professionals to better understand the scope and impact of social media in healthcare, and assists them to adopt and harness social media effectively, and maximize the benefits for the specific needs of the clinical community.